African seminar on problems of drug dependence. Lagos, Nigeria ; 26th-28th november 1980 : proceedings - Anumonye, A.; Tongue, Archer; Tongue, Eva; Vincze, A.; International Council on Alcohol and Addictions (Lausanne : International Council on Alcohol and Addictions, 1980)
Samenvatting van het congres over drugsproblematiek dat in 1980 plaats had in Lagos, Nigeria.